1961
DOI: 10.1097/00010694-196101000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Leaky Artesian Aquifer Conditions in Illinois

Abstract: the average vertical permeability of the Maquoketa Formation in northeastern Illinois is about 0.00005 gpd per square foot. Leakage in 1958 through the Maquoketa Formation in northeastern Illinois is estimated to be about 8,400,000 gpd or about 11 per cent of the water pumped from deep wells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1966
1966
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 6 publications
(2 reference statements)
1
23
0
Order By: Relevance
“…In hydrologic engineering the revealing of leakage through multiple aquifer systems is connected to Witherspoon (1969, 1972 November 6, 1965) In the natural sciences branch of hydrogeology the theoretical benchmarks of development were: Tóth (1963Tóth ( , 1978, Tóth and Millar (1983), Witherspoon (1966, 1967) and Zijl and Nawalany (1993). The empirical approach was used by Walton (1960), Kolesov (1965), Mifflin (1968), Margat (1969), Erdélyi (1976) and Ortega and Farvolden (1989) (Fig. 4).…”
Section: The Artesian and The Basin Hydraulic Paradigm In The Overallmentioning
confidence: 99%
“…In hydrologic engineering the revealing of leakage through multiple aquifer systems is connected to Witherspoon (1969, 1972 November 6, 1965) In the natural sciences branch of hydrogeology the theoretical benchmarks of development were: Tóth (1963Tóth ( , 1978, Tóth and Millar (1983), Witherspoon (1966, 1967) and Zijl and Nawalany (1993). The empirical approach was used by Walton (1960), Kolesov (1965), Mifflin (1968), Margat (1969), Erdélyi (1976) and Ortega and Farvolden (1989) (Fig. 4).…”
Section: The Artesian and The Basin Hydraulic Paradigm In The Overallmentioning
confidence: 99%
“…Application of Walton's (1970) formula using an estimate of vertical hydraulic conductivity of 5X10-5 (gal/d)/ft2 (7X10-11 ft/s) given by Walton (1960) for the Maquoketa Shale in Illinois, which is assumed to be lithologically similar to the Northview Shale, yields an estimated annual leakage of approximately 3 billion gallons over the entire 735 square-mile area. The method of downward-leakage computation is described in the "Supplemental Information" section at the end of this report.…”
Section: Effects Of Abandoned Mines On Ground-water Hydrologymentioning
confidence: 99%
“…However, it is assumed that it would have similar values to those in northeastern Illinois and southeastern Wisconsin. In northeastern Illinois, Walton (1960) Through a series of model calibration adjustments, it was found that a vertical hydraulic conductivity of 0.000004 ft/d divided by the thickness for most of confining bed 3 provided the best match between observed and computed potentiometric heads. On the western side of the model area, where the Maquoketa Shale is not present and the Galena-DecorahPlatteville unit is less than 80 ft thick, a vertical hydraulic conductivity of 0.0001 ft/d provided the best match between the observed and model-computed potentiometric heads.…”
Section: Leakance Of the Confining Bedsmentioning
confidence: 99%
“…In northeastern Illinois, the vertical hydraulic conductivity of the drift calculated from seven aquifer tests ranged from 0.01 to 0.084 ft/d (Walton, 1960 Table 3 includes high-capacity-well pumpage from aquifers 1,2, and 3 only. The State of Wisconsin classifies a high-capacity well as one which has the capability of producing at least 100,000 gal/d.…”
Section: Leakance Of the Confining Bedsmentioning
confidence: 99%